ADMINISTRATION OF JUSTICE DURING THE COVID-19 PANDEMIC AND THE RIGHT TO A FAIR TRIAL (EU and comparative law issues and challenges series (ECLIC), 2021)
On 11 March 2020 the World Health Organization announced the Covid-19 (coronavirus) to be a pandemic. To combat the pandemic, many countries had to adopt emergency measures and some of these measures have affected the judicial system, especially the functioning of courts. The pandemic has been characterised as far as the judiciary is concerned by complete or partial closure of court buildings for the parties and for the public. It is clear that the functioning of national judicial systems has been severely disrupted. This limited functioning of courts impacted the individuals’ right to a fair trial guaranteed, in particular, under Article 6 of the European Convention on Human Rights. The aim of this article is to examine the manner of the administration of justice during the Covid pandemic and its impact on the due process guarantees. Focus is put on the extent to which different Covid measures, in particular remote access to justice and online hearings have impacted the guarantees of the right to a fair trial and the due process guarantees in general, notably in detention cases. In this connection, the article provides a comparative overview of the functioning of the European legal systems during the pandemic. It also looks into the way in which the two European courts – the European Court of Human Rights and the Court of Justice of the European Union functioned, as well as the way in which the Croatian courts, including the Constitutional Court, organised their work during the pandemic. The article then provides an insight into the issue of online/remote hearings in the case-law of the European Court of Human Rights and in the Croatian Constitutional Court’s case-law. On the basis of this assessment, the article identifies the differences in the use of remote/online hearings between and within jurisdictions. In conclusion, the article points to some critical considerations that should be taken into account when devising the manner in which any Covid pandemic experience with the administration of justice (notably with regard to remote/online hearings) can be taken forward.